Extending beyond Gondwana: Cretaceous Cunoniaceae from western North America. Issue 2 (10th February 2022) - Tang, Keana K.; Smith, Selena Y.; Atkinson, Brian A.
Summary: Cunoniaceae are important elements of rainforests across the Southern Hemisphere. Many of these flowering plants are considered Paleo‐Antarctic Rainforest Lineages that had a Gondwanan distribution since the Paleocene. Fossils of several modern genera within the family, such as Ceratopetalum, have indicated biogeographical connections between South America and Australia in the Cenozoic. Here, we report a dramatic geographical range extension for Ceratopetalum, and Cunoniaceae as a whole, based on two exceptionally preserved fossil winged fruits from Campanian ( c . 82–80 Ma old) deposits on Sucia Island, Washington, USA. The fossils were studied using physical sectioning, light microscopy, micro‐computed tomography scanning and multiple phylogenetic analyses. The fossil fruits share diagnostic characters with Ceratopetalum such as the presence of four to five persistent calyx lobes, a prominent nectary disk, persistent stamens, a semi‐inferior ovary and two persistent styles. Based on morphological comparisons with fruits of extant species and support from phylogenetic analyses, the fossils are assigned to a new species Ceratopetalum suciensis . These fossils are the first unequivocal evidence of crown Cunoniaceae from the Cretaceous of North America, indicating a more complicated biogeographical history for this important Gondwanan family.